Volatilitas Market Cap Pada BEI Periode 2019-2021 - Amalia, Naili; Sunarso, Sunarso (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Stocks are indeed one of the most eye-catching investments for investors. As an investor, you need clear directions regarding the volatility of each layer of the market cap of stocks. Knowing the volatility of each layer of the market cap will provide consideration for investors before making an investment. This will involve considering the amount of return and risk that will be faced. The higher the volatility of stock prices, which gives a signal, the higher the risks that will be faced. Lower volatility signals that companies tend to have a higher market cap and lower risk. This research method uses quantitative methods with descriptive analysis and uses secondary data. The population of this study is the shares of companies listed on the IDX from 2019 to 2021, taken by purposive sampling, where at each layer of the market cap there are 30 companies. The results showed that there was a significant difference in the value of volatility in the market cap layer. While the results of risk and stock returns for each layer of market cap have differences but are not significant.